Organizational Performance In The Context Of Talent And Knowledge Management: The Mediating Role Of Employee Retention - Prasetyo Moelyadi, Iman; Fauzi, Akhmad; Anwar, Muhadjir (Dinasti Publisher, 2025)
Enhancing organizational performance necessitates the effective implementation of talent management and knowledge management strategies to foster competitive advantage through the development of employee skills and competencies. This study aims to examine the influence of talent management and knowledge management on organizational performance, and to investigate the mediating role of employee retention in this relationship. The study involved a population of 157 managerial-level employees at PT Pertamina Patra Niaga, from which a sample of 113 respondents was selected using simple random sampling. Primary data were collected through structured questionnaires and analyzed using the Partial Least Squares (PLS) method. The findings reveal that (1) both talent management and knowledge management exert a positive and significant influence on organizational performance; (2) employee retention does not mediate the relationship between talent management and organizational performance; and (3) employee retention significantly mediates the effect of knowledge management on organizational performance